O processo de urbanização de Mossorò: dos processos históricos à estrutura urbana atual - Pinheiro, Karisa Lorena Carmo Barbosa (2006)
The general objective of this academic work is to analyze the relationship between the territorial division and the urban expansion process of Mossoró city, understood here as the production and occupation of space. The urban expansion in Mossoró, since its formation as settlement in 1772 until current days, identifies with the Brazilian urbanization process whose growth is determined by the capitalist development. Thus, the expansion was determined by several economical specializations imposed by the territorial division of work which occurs at an interregional level, and, sometimes at an international level. Then, each specialization determined a moment of the urban expansion of the city, as follows: a) The cattle farmer specialization, between 1772 and 1857, when the urban expansion was shy, is summarized to a commercial square that received goods from Aracati aiming to cover a wide rural area; b) The commercial emporium specialization, between 1857 and 1930, when the urban expansion took an important impulse with the concentration of public and private capitals; c) The salt industry and the agricultural-industrial exporter specialization inside a state of development policy, between 1930 and 1970, when the urban expansion, joined to the settlement of the working class in the urban soil, developed along an important axis -the railway; d) The render of services specialization inside a state of intervention policy, between 1970 and 1990, when the urban expansion was characterized by the accelerated growth rhythm, by the reuse of some spaces, and by space segregation of demanding people; e) The render of services policy inside a neoliberal state policy, since 1990 until current days, when the urban expansion reduced its rhythm abruptly, when only small alterations occurred in the existing spaces. It focused on social policies and on several slums eradication programs. Finally, the territorial structure is deeply articulated with others, no territorial, but economical, social and political, which happens at a national, regional and local rate. Only within a historical and conceptual panorama, it was possible to explain the urban expansion in Mossoró from its formation in 1772 until current days. Therefore, this work is a several discipline analysis of the urbanization process existing in Mossoró